EVALUATION IN THE STEP BY STEP EDUCATIONAL ALTERNATIVE - ACTION - RESEARCH - HORAŢIU CATALANO; MIRELA BOCA (Studia Universitatis Babes-Bolyai, 2014)
ABSTRACT. This study aims at valorising the theoretical and practical premises of evaluation in general and of the Step by Step educational alternative in particular. The hypothesis from which we departed focuses on the idea according to which the evaluative strategies specific to the Step by Step educational alternative constitute motivating and mobilising factors for learning. By means of our study we aimed at detecting the strengths, the weaknesses, the evaluative strategies specific to the Step by Step alternative and the determination of the emotional impact of the various evaluative strategies at the level of the pupils.